The analysis of risks inherent in external fire escape stairs, through a new model proposal - Avlar, Erkan; Yildirim, Husniye Sueda (GAZI UNIV, FAC ENGINEERING ARCHITECTURE, 2020)
A number of fire safety hazards affect the buildings, due to the existence and prevalence of certain access and use-issues with external fire escape stairs. The purpose of the present study is to help eliminate or minimize the sources of hazards on external fire escape stairs, and to restrain their effects on users. The study entails a new proposed risk analysis model to identify the specific sources of hazards involved, and come up with solutions, in the context of the regulations to be introduced for the prevention of hazards on the external fire escape stairs of existing buildings. The model was tested through a field study performed in 10 districts of Istanbul, culminating in the observation of a high level of risks inherent in external fire escape stairs. The findings reached show that the proposed model can be applied successfully in terms of assessing the sources of hazards on external fire escape stairs with reference to the number of buildings and the scale of hazards, as well as in the context of analyzing the risks and developing accurate solutions for the hazards
Keywords: Fire safety; external fire escape stairs; risk analysis model DKM-RAM; SAFETY; Engineering